+0  
 
0
18
1
avatar

Find all real values of x such that

(2x^2 - 3x)/(x^2 - x) + 5x - 11 = (3x^2 + 4)/(x^2 - 1)

 Jun 1, 2021
 #1
avatar
+1

\(\frac{2x^{2}-3x}{x^{2}-x}+5x-11=\frac{3x^{2}+4}{x^{2}-1}\) (Problem)

 

\(\frac{x(2x-3)}{x(x-1)}+5x-11=\frac{3x^{2}+4}{(x+1)(x-1)}\)  (Factor out the x and expand \(x^{2}-1\))

 

\(\frac{2x-3}{x-1}+5x-11=\frac{3x^{2}+4}{(x+1)(x-1)}\)   (Cancel the x)

 

\((2x-3)(x+1)+5x(x-1)(x+1)-11(x-1)(x+1)=3x^{2}+4\)  (Multiply everything by (x-1)(x+1) to get rid of the denominator on the right hand side)

 

\((2x^{2}-x-3)+(5x^{3}-5x)-(11x^{2}-11)=3x^{2}+4\)  (Expand)

 

\(5x^{3}-9x^{2}-6x+8=3x^{2}+4\)   (Simplify)

 

\(5x^{3}-12x^{2}-6x-4=0\)   (Simplify)

 

I hope you can take it from here!

 Jun 2, 2021

44 Online Users

avatar
avatar
avatar
avatar
avatar
avatar